Administrative Strategies of Police Partners in the Scope of Legal Administration to Reduce Illegal Levies - Agus Salim (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Illegal levies (pungutan ilegal) remain a persistent challenge within Indonesia’s public administration and law enforcement systems, undermining transparency, democratic values, and public trust. This study examines administrative strategies involving police partners and community participation as preventive mechanisms to reduce illegal levies in public institutions. Employing a qualitative descriptive approach, the research analyzes citizen-based investigative training, complaint-handling mechanisms, and collaborative governance models that empower citizens to observe, document, and report administrative irregularities in partnership with law enforcement agencies. The findings reveal that citizen-based investigations, supported by structured training and institutional frameworks such as Senkom Mitra Polri, significantly enhance transparency and administrative accountability. Community–police synergy not only strengthens early detection of illegal levies but also contributes to maintaining public order and restoring confidence in public institutions. Furthermore, the integration of digital reporting systems and consistent administrative supervision reduces opportunities for manipulation and supports standardized service procedures. This study concludes that the effectiveness of anti-illegal levy strategies depends on sustained institutional commitment, legal protection for citizen reporters, and continuous public education. Strengthening administrative law frameworks that institutionalize community participation and police partnerships is essential for fostering transparent, accountable, and democratic public governance in Indonesia.